2001
DOI: 10.1029/2000ja003005
|View full text |Cite
|
Sign up to set email alerts
|

Origins of energetic ions in the cusp

Abstract: Abstract. Recent studies reported on a new magnetospheric phenomenon called cusp energetic particle (CEP) events. It has been suggested that these energetic particles with significant fluxes up to several hundred keV/e are accelerated locally in the cusp. An alternative explanation for the energetic particle events is that they are accelerated at the quasi-parallel bow shock, then transported downstream and enter the cusp along newly reconnected field lines or some other solar wind entry mechanism. It is well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
138
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(146 citation statements)
references
References 50 publications
8
138
0
Order By: Relevance
“…cusp (Lin et al, 2007) showing these ions have access to the cusp. Further evidence was provided by Trattner et al (2001) who analyzed the ion abundance ratios and concluded these were also consistent with what would be expected with the bow shock. If the quasi-parallel bow shock is the primary source for energetic ions in the cusp and local energization is not occurring, an additional source would have to provide the observed energetic electron or ionospheric ion populations.…”
Section: Introductionmentioning
confidence: 84%
“…cusp (Lin et al, 2007) showing these ions have access to the cusp. Further evidence was provided by Trattner et al (2001) who analyzed the ion abundance ratios and concluded these were also consistent with what would be expected with the bow shock. If the quasi-parallel bow shock is the primary source for energetic ions in the cusp and local energization is not occurring, an additional source would have to provide the observed energetic electron or ionospheric ion populations.…”
Section: Introductionmentioning
confidence: 84%
“…The energy range for CEP is from about 20 keV to 10 MeV Fritz et al, 2003). Trattner et al (2001) claimed that the CEPs with energies <150 keV were from the quasi-parallel bow-shock and that while those CEPs with energies >150 keV were from the radiation belt. The present study shows that the 24-44.5 keV CEPs are also not from the bow shock.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Fritz et al (2003) by comparing the time-intensity profiles of O ≤+2 and He ++ ions pointed out that since the seed population of the cusp energetic O ≤+2 is of ionospheric origin, and since the seed population of the cusp energetic He ++ is solar wind plasma, the similarity of their profiles suggests that both seed populations are energized by a common acceleration mechanism active in the polar cusp. Although there are many indications of local particle acceleration in the cusp this view has been questioned I. I. Vogiatzis et al: Supra-thermal particle acceleration in the cusp region 655 by Trattner et al (2001) who provided an alternative explanation for the cusp energetic particles, suggesting that they are accelerated at the quasi-parallel bow shock, then being transported downstream and entering the cusp along newly reconnected field lines or some other solar wind entry mechanism.…”
Section: Introductionmentioning
confidence: 99%